1974
DOI: 10.1128/iai.9.2.377-383.1974
|View full text |Cite
|
Sign up to set email alerts
|

CAMP Factor of Group B Streptococci: Production, Assay, and Neutralization by Sera from Immunized Rabbits and Experimentally Infected Cows

Abstract: Quantitative assay methods for CAMP factor activity of group B streptococci and for neutralization of this activity by animal sera are described. The course of the CAMP reaction is influenced by preincubation of red cells with staphylococcal beta-hemolysin and the rate of the reaction by the concentration of CAMP factor. The production of CAMP factor is enhanced by substitution of maltose for glucose in culture broth. Rising inhibitory titers to CAMP activity in sera of rabbits injected with sterile culture su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…2) suggests that two different complexes with different dissociation constants exist under given conditions . Moreover, it should be mentioned that an additional type of protein B/Ig complex is formed by the interaction of protein B with specific antibodies (29), which exhibit true determinant specificities for the protein B. Preliminary experiments indicated that an immunoprecipitate is obtained in agar gel diffusion using purified protein B and antibodies raised against purified protein B in the rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…2) suggests that two different complexes with different dissociation constants exist under given conditions . Moreover, it should be mentioned that an additional type of protein B/Ig complex is formed by the interaction of protein B with specific antibodies (29), which exhibit true determinant specificities for the protein B. Preliminary experiments indicated that an immunoprecipitate is obtained in agar gel diffusion using purified protein B and antibodies raised against purified protein B in the rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…Assay of CAMP activity. CAMP activity was assayed by a modification of the method of Brown et al (7). Starting with 0.5 ml, volumes of test solution decreasing by about 25% were placed in tubes (12 by 75 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Brown et al (7) showed that sheep erythrocytes preincubated with staphylococcal sphingomyelinase, washed, and then exposed to CAMP protein underwent lysis, whereas sheep erythrocytes exposed to CAMP protein, washed, and then exposed to staphylococcal sphingomyelinase did not lyse. These results indicate that CAMP protein reacts with erythrocytes modified by sphingomyelinase but not with untreated erythrocytes.…”
Section: A B Fig 3 (A)mentioning
confidence: 99%
“…An ancillary factor for the identification of group B streptococci, long utilized in veterinary microbiology, is the CAMP factor, named for the scientists originally describing the phenom- enon (33). The CAMP factor is thought to be a diffusable, heat-stable extracellular protein of group B organisms that enhances rapid hemolysis of sheep erythrocytes by staphylococcal beta-hemolysin (25,47). Classically, the reaction is produced by streaking the staphylococcal strain across the diameter of a sheep blood agar plate, and the streptococcal strains to be assayed perpendicular to the staphylococcal streak.…”
Section: Downloaded Frommentioning
confidence: 99%